Konfetti i hela min säng. En studie av prisnominerade skönlitterära debutanter 2010–2020 - Kvist, Lena (2022)
This master’s thesis aims to investigate how literary prize nominated first-time fiction writers experience the circumstances around publishing their debut work, with particular focus on the significance of literary awards. The study is based on semi-structured interviews with ten debut authors from the 2010’s: Tomas Bannerhed, Anna Fock, Tove Folkesson, Carolina Fredriksson, Marit Kapla, Agnes Lidbeck, Sami Said, Karin Smirnoff, Stina Stoor, Isabelle Ståhl. The ten authors have been nominated for and/or awarded one or several of the prizes Borås Tidnings Debutantpris, Katapultpriset and Augustpriset. The investigation shows that the authors put significant effort into their debut work of fiction and that being published is a life-changing experience for them. Being nominated for the prestigious prizes gives the authors distinctive economic capital as well as cultural capital in a bourdieusian sense. When the new authors are acknowledged by media, they also acquire journalistic capital that supports them in creating a position within the literary field. The authors’ identities change in the eyes of others, as they gain new identity capital when they succeed. The authors value their new capital and their new positions but play down the significance of economic capital. Freedom is an important keyword for them. After gaining all this new economic and symbolic capital the authors are free to keep writing. Some new obstacles might also occur: the spotlight on the authors makes the field’s expectations on their second work of fiction higher and the changes in positions can create situations where the authors experience that people start treating them differently, which can be alluring as well as repulsive to them. The thesis also highlights how being nominated in some cases can be as important as winning the awards.